Estimasi True Score dan Kesalahan Baku Pengukuran Tes Buatan Guru Bidang Studi Matematika Menurut Teori Tes Klasik pada Tingkat SMP - Rasmuin Rasmuin; Desy Rahayu (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2021)
Problem statement of this research was how estimation of true score and standard error measurement of teacher made test mathematics subject according to classical test theory at the Junior High School level in Baubau city. Objective of this research was to know estimation of true score and standard error measurement of teacher made test Mathematics subject according to classical test theory at the Junior High School level in Baubau city. This research was descriptive quantitative research with the research subjects were all multiple choice tests made by the teacher for the final even semester test for the student at class VIII academic year of 2020/2021 in Mathematics subject of 7 Junior High School in Baubau city. The instruments of this research were answer sheets and student answer keys which were collected using documentation techniques. Data analysis was using the ITEMAN program. The results showed that the measurement standard error (E) of the Mathematics teacher made test at the Junior High School level in Baubau city consisted of 7 relatively small schools, including SMP Negeri 1 Baubau of 2,224, SMP Negeri 3 Baubau of 2,680, SMP Negeri 5 Baubau of 2,005, SMP Negeri 7 Baubauof 2,147, SMP Negeri 9 Baubau of 1,450, SMP Negeri 11 Baubau of 1,883, and SMP Negeri 17 Baubau of 1,995. This showed that the observed score obtained by student (X) tends to be close to the actual score (T).